Deciphering the role of miRNA in reprogramming plant responses to drought stress. (19th May 2023) - Singh, Archana; Jain, Deepti; Pandey, Jyotsna; Yadav, Manisha; Bansal, Kailash C.; Singh, Indrakant K.
Abstract: Drought is the most prevalent environmental stress that affects plants' growth, development, and crop productivity. However, plants have evolved adaptive mechanisms to respond to the harmful effects of drought. They reprogram their: transcriptome, proteome, and metabolome that alter their cellular and physiological processes and establish cellular homeostasis. One of the crucial regulatory processes that govern this reprogramming is post-transcriptional regulation by microRNAs (miRNAs). miRNAs are small non-coding RNAs, involved in the downregulation of the target mRNA via translation inhibition/mRNA degradation/miRNA-mediated mRNA decay/ribosome drop off/DNA methylation. Many drought-inducible miRNAs have been identified and characterized in plants. Their main targets are regulatory genes that influence growth, development, osmotic stress tolerance, antioxidant defense, phytohormone-mediated signaling, and delayed senescence during drought stress. Overexpression of drought-responsive miRNAs (Osa-miR535, miR160, miR408, Osa-miR393, Osa-miR319, and Gma-miR394) in certain plants has led to tolerance against drought stress indicating their vital role in stress mitigation. Similarly, knock down (miR166/miR398c) or deletion (miR169 and miR827) of miRNAs has also resulted in tolerance to drought stress. Likewise, engineered Arabidopsis plants with miR165, miR166 using short tandem target mimic strategy, exhibited drought tolerance. Since miRNAs regulate the expression of an array of drought-responsive genes, they can act as prospective targets for genetic manipulations to enhance drought tolerance in crops and achieve sustainable agriculture. Further investigations toward functional characterization of diverse miRNAs, and understanding stress-responses regulated by these miRNAs and their utilization in biotechnological applications is highly recommended.